Construction Project Monitoring: The Cost and Schedule Control by Earned Value Method (EVM) - Hasan, Rakibul; Chowdhury, Showaib Ahmed; Akter, Jhumana (Journal of Technology Management and Business, 2021)
On account of ever increasing complexities and uncertainties, construction project management has become more and more challenging day by day. As a result, continuous project monitoring emerges as a prime concern for the planned activities to be completed on schedule and within budget. Limitations in traditional time and cost monitoring practices result in time and cost overrun which seriously hinder successful completion of a project. The impact of time and cost at various stages of a construction project is a critical factor in the project’s successful completion and management. Most of the construction projects in Bangladesh have completed with extra time which leads the demand of additional cost because of poor project monitoring and controlling system. In these consequences, a widely recognized emerging project monitoring technique, Earned Value Management (EVM) can be introduced to conduct project progress, performance and forecasting. EVM measures the actual work completed on a project at any time with respect to the original cost and schedule by integrating project scope, cost and schedule in order to predict cost and completion timeline. In this study, a three-storied residential building project at Khulna, Bangladesh was considered to perform earned value management for tracking whether the project is either delay or not along with either over budget or under budget at any particular day. The construction operations up to the first six months were assessed using an EVM based on a work-breakdown structure (WBS), in which the real activities and costs were compared to the projected program. The progress of the under constructed project considering cost and schedule were also evaluated through analyzing EVM indexes using Microsoft Project Professional 2019 software. Construction performance was assessed respecting cost variance (CV), schedule variance (SV), cost performance index (CPI) and schedule performance index (SPI). CV and CPI are evidently less than 0 and 1, respectively, indicating that the project was on the verge of cost overrun; on the other hand, SV and SPI are both less than 0 and 1, indicating that the project was running behind budget after six months. As a result, if this project is pursued at its current pace, it will be finished behind schedule and above budget. It will undoubtedly assist project rescheduling to bring the performance back to harmony.